MALDI-TOF mass spectrometry in microbiology - Kostrzewa, Markus; Schubert, Sören (Caister Academic Press, 2016)
In this timely and up-to-date book, experts in the field provide an overview of the application of MALDI-TOF MS in key areas of microbiology and discuss the impact this modern technology is having on laboratory practice and patient outcome. Several chapters cover applications in clinical and veterinary diagnostic laboratories, food microbiology, environmental microbiology and strain collections. Further chapters discuss the utilization of MALDI-TOF MS for the analysis of challenging microbial groups such as yeast and anaerobic bacteria. In addition, new applications such as microbial typing, D.